ANALYSIS OF CAPITAL STRATEGY AND CREDIT RISK MANAGEMENT IN INCREASING THE VALUE OF BANKING COMPANIES (A Study of State-Owned Banks Listed on the Indonesia Stock Exchange for the 2020–2025 Period) - Nurul Aulia; Erry Sunarya; Tetty Sufianty Zafar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Performing Loan/NPL) on firm value (Price to Book Value/PBV) in state-owned banks (Bank BUMN) listed on the Indonesia Stock Exchange during 2020–2025. The research is motivated by fluctuations and disparities in firm value among state-owned banks despite operating in a relatively homogeneous sector and regulatory environment, along with inconsistencies in prior studies. This study uses a quantitative method with an associative approach. The sample comprises five state-owned banks (BBRI, BMRI, BBNI, BBTN, BRIS) over six years (2020–2025), yielding 30 observations from annual reports. Data were analyzed using panel data regression with EViews 13, including model selection (Chow Test, Hausman Test), multicollinearity testing, and hypothesis testing (t-test, F-test, coefficient of determination). Results show the Random Effect Model (REM) as the best-fit model. Partially, CAR has a significant positive effect on firm value, while NPL has no significant effect. Simultaneously, CAR and NPL significantly affect firm value, with an R-squared of 28.52%. These findings support Signaling Theory, whereby high capital adequacy signals financial strength to investors, thereby increasing the bank's market valuation.